The Role of Neutrophil in The Pathophysiology of Frailty Syndrome - Muhammad Ghifari Rifanhsa; Ilsa Hunaifi; Ika Primayanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Neutrophils, also known as polymorphonuclear leukocytes, play a significant role in fueling systemic inflammation and tissue damage within the context of frailty, a clinical syndrome associated with increased susceptibility to stressors and decreased functional performance typically linked to aging. This literature review delves into the interplay between neutrophils and frailty, shedding light on their contribution to age-related systemic inflammation. The investigation explored the correlation between heightened neutrophil levels, diminished physical activity, increased frailty, and elevated white blood cell counts. These findings underscore the substantial role of neutrophils in the development of frailty, necessitating further research to enhance comprehension of their involvement for more effective prevention and intervention strategies. The implications of this study emphasize the importance of tailored exercise regimens, promoting optimal nutrition practices, efficiently managing chronic inflammation, and improving the control of chronic diseases as essential approaches to address frailty among older individuals.